38.0k views
1 vote
For the given statement Pn, write the statements P1, Pk, and Pk+1.

2 + 4 + 6 + . . . + 2n = n(n+1)

User Vinko
by
6.5k points

2 Answers

2 votes

P(n):2+4+6+\cdots+2n=\displaystyle\sum_(i=1)^n2i


P(1):\displaystyle\sum_(i=1)^12i=2=1(1+1)=2


P(k):\displaystyle\sum_(i=1)^k2i=2+\cdots+2k=k(k+1)


P(k+1):\displaystyle\sum_(i=1)^(k+1)2i=2+\cdots+2k+2(k+1)=(k+1)(k+2)
User Mnemonic
by
6.2k points
0 votes

Answer:


P_(1) = 2


P_(k) = k(k+1)


P_(k+1) = (k+1)(k+2)

Explanation:

We are given the statement,


P_(n) as 2 + 4 + 6 + . . . + 2n = n(n+1)

That is,


P_(n) as 2 + 4 + 6 + . . . + 2n =
\sum_(i=1)^(n)2i

So, we have,


P_(1) =
\sum_(i=1)^(1)2i = 2


P_(k) =
\sum_(i=1)^(k)2i = 2 + 4 + 6 + . . . + 2k = k(k+1)


P_(k+1) =
\sum_(i=1)^(k)2i = 2 + 4 + 6 + . . . + 2k + 2(k+1) = (k+1)(k+2)

Thus, we get,


P_(1) = 2


P_(k) = k(k+1)


P_(k+1) = (k+1)(k+2)